SYNTHESIS OF Mg/Al HYDROTALCITE-LIKE FROM BRINE WATER AND ITS APPLICATION FOR METHYL ORANGE REMOVAL: A PRELIMINARY STUDY (Makara Journal of Science, 2011)
The objective of this research is to synthesis of Mg/Al hydrotalcite-like (Mg/Al HTlc) from brine water and its application as a methyl orange (MO) removal. The research initiated with the synthesis of Mg/Al HTlc from brine water, which is well known as the desalination process wastewater. Characterization of the Mg/Al HTlc synthesized was confirmed through X-ray Diffraction and FT-IR Spectroscopy. The determination of optimum acidity, adsorption rate, and energy and capacity adsorption were studied. The result showed that pH 4 was the optimum acidity for the adsorption of MO on Mg/Al HTlc. MO was adsorbed at pseudo-second order adsorption rate of 1.03 × 105 g mol-1 min-1 on the Mg/Al HTlc. The adsorption data fitted well into the linearly transformed Freundlich equation.